Microbiological research and development for the food industry - Taormina, Peter J., 1973- (Boca Raton, Fla. : CRC Press, 2013)
'This book serves as a primer and reference for industrial food microbiologists who typically gain the information provided through on-the-job experience or from a consultant instead of in the classroom. The intent is to describe the purposes and processes for conducting microbiological research and development. A broad range of topics is covered including the basics of setting up a food microbiology laboratory, procedures for validating the efficacy of process and product food safety controls, practices and protocols for developing effective food preservatives, sanitizers and biocides, approaches to responding to food safety emergencies, predicting survival and growth of microbes in foods, and approaches to meaningful communication of food microbiology research outcomes'--
Includes bibliographical references and index.
Keywords: Food -- Microbiology; Food industry and trade